Auricular acupoint sticking and pressing therapy and nursing management for a patient with intractable urinary retention (耳穴贴压治疗顽固性尿潴留1例护理体会) - FENG Jiangxue (冯江雪); LI Yixuan (李怡璇); LIU Pan (刘盼); LIU Bo (刘博); SUN Junyi (孙均意) (中西医结合护理)
This paper summarized the auricular acupoint sticking and pressing therapy and related nursing management for a patient with intractable urinary retention. Nurses comprehensively assess the medical condition of the patient before carring out nursing interventions such as dietary guidance, health education on defecation, wound care, and psychological care. Based on syndrome differentiation of Traditional Chinese Medicine, auricular acupoint sticking and pressing therapy was carried out to relieve the symptoms of urinary retention and pain, and improve the sleep quality and postoperative recovery. (本文总结耳穴贴压治疗顽固性尿潴留1例的效果及中西医结合护理体会。护理人员完善护理评估, 基于中医辨证分型, 在饮食调护、排便指导、伤口护理、心理干预等常规护理措施基础上, 采用耳穴贴压中医适宜技术, 有效改善患者尿潴留症状, 缓解疼痛, 提高睡眠质量, 促进术后早期康复。)